Current GMP standards for the large-scale production of monoclonal antibodies - (:unkn) unknown (WILEY, 2026)
Monoclonal antibodies have revolutionized modern medicine due to their target-specific properties and effectiveness in treating a wide range of diseases, including cancer, autoimmune disorders, infectious diseases, and neurological conditions. Importantly, their large-scale production for human use requires strict adherence to good manufacturing practice (GMP) standards to ensure quality, safety, and efficacy. This article reviews key aspects of monoclonal antibody production under GMP standards, from cell-line selection to culture strategies, antibody purification, formulation, and quality control processes. Additionally, we discuss the significance of validation and traceability in production, as well as the implementation of emerging technologies to enhance manufacturing efficiency and safety. Despite progress in bioprocesses and regulatory frameworks, several challenges, such as batch-to-batch variability, high production costs, and the need to continuously adapt processes to new regulations, remain to be solved. The integration of innovative approaches with evolving regulations will enable the optimization of monoclonal antibody production and ensure their global accessibility.
Keywords: bioprocesses; good manufacturing practices (GMPs); monoclonal antibodies (mAbs); pharmaceutical regulation; quality control